2019
DOI: 10.1097/inf.0000000000002392
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Ceftazidime-Avibactam Plus Metronidazole in the Treatment of Children ≥3 Months to <18 Years With Complicated Intra-Abdominal Infection: Results From a Phase 2, Randomized, Controlled Trial

Abstract: Background: Ceftazidime-avibactam plus metronidazole is effective in the treatment of complicated intra-abdominal infection (cIAI) in adults. This single-blind, randomized, multicenter, phase 2 study (NCT02475733) evaluated the safety, efficacy and pharmacokinetics of ceftazidime-avibactam plus metronidazole in children with cIAI. Methods: Hospitalized children (≥3 months to <18 years) with cIAI were randomized 3:1 to receive intravenous ceftazidime-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 21 publications
2
41
0
4
Order By: Relevance
“…The safety profile in one phase I trial and two phase II trials including children from 3 months to 18 years of age was similar to that observed in the adult population (72)(73)(74). Based on the results from these trials, the Food and Drug Administration (FDA) has recently approved its use in pediatric patients Ͼ3 months of age with complicated intra-abdominal infections (cIAIs), in conjunction with an agent active against anaerobic organisms, and also those with urinary tract infections (UTIs).…”
Section: Treatmentsupporting
confidence: 60%
“…The safety profile in one phase I trial and two phase II trials including children from 3 months to 18 years of age was similar to that observed in the adult population (72)(73)(74). Based on the results from these trials, the Food and Drug Administration (FDA) has recently approved its use in pediatric patients Ͼ3 months of age with complicated intra-abdominal infections (cIAIs), in conjunction with an agent active against anaerobic organisms, and also those with urinary tract infections (UTIs).…”
Section: Treatmentsupporting
confidence: 60%
“…Se observaron respuestas clínicas/microbiológicas favorables en el ≥90 % de los pacientes en ambos grupos de tratamiento al final de este. Como conclusión, la CAZ-AVI más metronidazol fue bien tolerada, con un perfil de seguridad similar a la ceftazidima sola, y pareció ser efectiva en pacientes pediátricos con infección por gramnegativos, incluidas cepas no susceptibles a ceftazidima (27).…”
Section: Ceftazidima-avibactam En Niñosunclassified
“…Among the avibactam conjugates, ceftazidime-avibactam has been used in Europe and the United States for the treatment of adults with complicated urinary tract infections (e.g., pyelonephritis and hospital-acquired pneumonia). It is also approved recently by the European Drug Administration for adult patients infected with aerobic Gram-negative bacteria with limited treatment regimen [ 38 , 69 ]. Meropenem-vaborbactam is the first carbapenem/ β -lactamase inhibitor conjugate recently approved by the US Food and Drug Administration (FDA) for the treatment of complicated urinary tract infections and acute pyelonephritis [ 39 , 40 ].…”
Section: Antibiotic-antibiotic Conjugates (Aacs)mentioning
confidence: 99%